ANALISIS PERAN GURU BIMBINGAN DAN KONSELING DALAM MENGEMBANGKAN SELF CONFIDENCE MELALUI BIMBINGAN KELOMPOK DI SMA NEGERI 1 JOGOROGO NGAWI TAHUN PELAJARAN 2021/2022 - Ambarwati, Kristina (MEDI KONS: Jurnal Prodi Bimbingan dan Konseling UNISRI Surakarta, 2022)
ABSTRACT Kritina Ambarwati. : AN ANALYSIS OF THE ROLE OF GUIDANCE AND COUNSELING TEACHERS IN MANAGING SELF CONFIDENCE THROUGH GROUP GUIDANCE AT SMAN 1 JOGOROGO IN 2021/2022 ACADEMIC YEAR. Thesis: Surakarta. Teacher Training and Education Faculty, Slamet Riyadi University, June 2022. The purpose of this study was to determine the steps taken by guidance and counseling teachers in developing student self-confidence at SMAN Jogorogo Ngawi, to determine the inhibiting factors of guidance and counseling teachers in developing self-confidence through group guidance at SMAN 1 Jogorogo Ngawi, to find out the supporting factors of guidance and counseling teachers in developing self-confidence through group guidance at SMAN 1 Jogorogo Ngawi, and to determine the impact of this development after group guidance by guidance and counseling teachers in developing self-confidence at SMAN 1 Jogorogo Ngawi. The research method used was descriptive qualitative through interviews with guidance and counseling teachers and was used as primary data. Furthermore, it was supported by students and teachers in these subjects as secondary data. Based on the results of the study, it could be concluded that the steps taken by guidance and counseling teachers were to optimize self-confidence for students through group guidance services so that it was expected to change the self-confidence that existed in students at SMAN 1 Jogorogo. The inhibiting factors of guidance and counseling teachers in managing self-confidence at SMAN 1 Jogorogo were students who were less willing to change themselves as individuals who have self-confidence and the many problems in their lives such as broken home factors, peer factors, and factors that existed in their lives. The supporting factor in providing this service was the awareness of the students themselves, because according to the guidance and counseling teacher at SMAN 1 Jogorogo, if there was no awareness from the students themselves, self-confidence efforts would not run smoothly. The impact that arose after the counseling service was carried out by the teacher was the presence of influential students and students who were not influential. Influential students tended to change their attitudes while students who were not influential will felt normal with the service. Keywords: Analysis of the Role of Guidance and Counseling Teachers, Self Confidence, Group Guidance